2014
DOI: 10.1007/s10114-014-3743-x
|View full text |Cite
|
Sign up to set email alerts
|

Cohomology of the Schrödinger algebra S(1)

Abstract: We explicitly compute the first and second cohomology groups of the Schrödinger algebra S(1) with coefficients in the trivial module and the finite-dimensional irreducible modules. We also show that the first and second cohomology groups of S(1) with coefficients in the universal enveloping algebras U (S(1)) (under the adjoint action) are infinite dimensional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For example, all derivations of the Schrödinger algebra determined and it is shown that this algebra admits an outer derivation (see [22]). Moreover, the first and second cohomology groups of the Schrödinger algebra in (1 + 1)-dimensional space time, with coefficients in the trivial module and the finite-dimensional irreducible modules are computed [21]. The adjoint cohomology and central extension of the Schrödinger algebra in (n + 1)-dimensional space time, are investigated in [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, all derivations of the Schrödinger algebra determined and it is shown that this algebra admits an outer derivation (see [22]). Moreover, the first and second cohomology groups of the Schrödinger algebra in (1 + 1)-dimensional space time, with coefficients in the trivial module and the finite-dimensional irreducible modules are computed [21]. The adjoint cohomology and central extension of the Schrödinger algebra in (n + 1)-dimensional space time, are investigated in [6].…”
Section: Introductionmentioning
confidence: 99%